Rapid Device‐Detected Nonsustained Ventricular Tachycardia in the Risk Stratification of Hypertrophic Cardiomyopathy. Issue 7 (4th May 2016) - VISWANATHAN, KARTHIK; SUSZKO, ADRIAN M; DAS, MOLOY; JACKSON, NICHOLAS; GOLLOB, MICHAEL; CAMERON, DOUGLAS; SPEARS, DANNA; WOO, ANNA; RAKOWSKI, HARRY; KHURANA, MAMTA; CHAUHAN, VIJAY S
Abstract : Background: Nonsustained ventricular tachycardia (NSVT) detected by ambulatory Holter (Holter NSVT) is a major risk factor for sudden cardiac death in hypertrophic cardiomyopathy (HCM). We hypothesized that the prognostic utility of Holter NSVT in HCM would improve with prolonged monitoring and a higher heart rate cut‐off for detection. Methods: We enrolled 60 patients (44 ± 14 years) with HCM, who had a prophylactic implantable cardioverter defibrillator (ICD). Positive Holter NSVT (prior to implant) was defined as ≥3 beats at ≥120 beats per minute (bpm). We assessed the prevalence of rapid NSVT (RNSVT) detected by their ICD within 12 months of its implant, defined as 4–16 beats at ≥150–200 bpm. The primary outcome was appropriate ICD therapy (antitachycardia pacing and shocks) for sustained ventricular arrhythmia (VA). Results: Holter NSVT was detected in 34 patients. RNSVT occurred in 21 (35%) patients of whom five did not have Holter NSVT. Over a median follow‐up of 61 (interquartile range 29, 129) months after ICD implant, nine patients had VA. RNSVT, but not Holter NSVT, was significantly associated with VA (hazard ratio 6.2, 95% confidence interval [1.3–30], P = 0.01) by multivariable Cox regression analysis that included conventional risk factors. Receiver operating characteristic analysis for RNSVT (area under curve 0.80, P = 0.005) showed that the occurrence of ≥2 episodes of RNSVT discriminated patients for VA optimally (sensitivity 78%, specificity 84%, positive predictive value 47%, negative predictive value 96%). Conclusions: In this pilot study, RNSVT detected by continuous monitoring independently predicted VA in HCM and offered superior discrimination of VA risk compared to conventional risk factors, including Holter NSVT. Future studies are needed to validate these findings in a larger, unselected HCM cohort.